The Oxford Handbook of Intellectual Disability and Development 2012
DOI: 10.1093/oxfordhb/9780195305012.013.0018
|View full text |Cite
|
Sign up to set email alerts
|

The Assessment and Presentation of Autism Spectrum Disorder and Associated Characteristics in Individuals with Severe Intellectual Disability and Genetic Syndromes

Abstract: This chapter considers the prevalence and nature of Autism Spectrum Disorders (ASD) and associated symptomatology in the intellectual disability population, with particular focus on three genetically determined syndromes—Fragile X syndrome, Tuberous Sclerosis Complex, and Rett syndrome—that have received particular attention with respect to their association with ASD. It then considers the importance of accurate assessment and diagnosis of ASD in individuals with genetically determined syndromes. It describes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 159 publications
(135 reference statements)
1
25
0
Order By: Relevance
“…Our data support findings from studies of subjects with genetic disorders (Moss et al, 2011) and individuals with intellectual disability (de Bildt et al, 2004) that cognitive impairments can confound the assessment for autism symptoms. In particular, we observed that lower cognitive functioning was associated with higher ADI-R social and communication domain scores, and after adjustment for cognitive functioning, there were no significant differences between BDNF+/− and BDNF+/+ subjects for any ADI-R domain.…”
Section: Discussionsupporting
confidence: 83%
“…Our data support findings from studies of subjects with genetic disorders (Moss et al, 2011) and individuals with intellectual disability (de Bildt et al, 2004) that cognitive impairments can confound the assessment for autism symptoms. In particular, we observed that lower cognitive functioning was associated with higher ADI-R social and communication domain scores, and after adjustment for cognitive functioning, there were no significant differences between BDNF+/− and BDNF+/+ subjects for any ADI-R domain.…”
Section: Discussionsupporting
confidence: 83%
“…The recommendation not to use genetic testing as part of routine diagnosis is based on current evidence, as the causal association between ASD and genetic disorders remains uncertain (Moss et al, 2011). Whilst neurological and genetic differences in ASD are increasingly well studied (Jordan and Murphy, 2011;Geschwind, 2011) current research has yet to be usefully applied to clinical practice.…”
Section: Genetic Testingmentioning
confidence: 99%
“…Previous comparisons of individuals with ASD with or without an associated syndrome (or a de novo mutation of potential pathogenic significance) are limited by the difficulty of identifying appropriate controls with idiopathic ASD (10). Individuals with neurogenetic syndromes with ASD often have significantly lower cognitive abilities than those with only ASD or only the neurogenetic syndrome, making it difficult to interpret direct comparisons on behavioral measures (13). Because ASD symptom measures are strongly influenced by IQ, comparing ASD severity across cognitive ability is particularly problematic (14).…”
Section: Introductionmentioning
confidence: 99%